The Effect of Risk Management and E-Filing Usage on Tax Compliance Costs: A Study on Small and Medium-Sized Enterprises in Padang, Indonesia - Fauziati , Popi; Azlina Md Kassim, Aza (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the influence of risk management and E-filing usage on tax compliance costs. The population of the study consist of taxpayers of registered Small Medium Enterprises (SMEs) in Padang, Indonesia. Purposive sampling technique was used to select the respondents. Regression analysis was used to examine the hypothesis. The study found that risk management have effect to tax compliance costs, meanwhile Efiling usage have no effect on tax compliance cost. The study recommended tax officers to provide more information on the use of E-filing. This can be done by socializing and providing taxpayers facilities. The socialization can be a simulation of the use of E-filing to taxpayers.